Representação social e avaliações do curso de pedagogia da UnB: os motivos, os valores e os interesses dos alunos - Bareicha, Paulo Sergio; Abreu, Alexandra; Carvalho, Alzenira de; Machado, Marta (Linhas Críticas, 1997)
Resumo